Efficacy of Trichoderma spp. and Kosakonia sp. Both Independently and Combined with Fungicides against Botrytis cinerea on Strawberries - Tom E. Schierling; Wolfgang Vogt; Ralf T. Voegele; Abbas El-Hasan (MDPI AG, 2024)
Background: The ascomycete Botrytis cinerea is a major pathogen of strawberry, often causing grey mold and significant yield losses. Its management has largely relied on chemical fungicides, which, while effective, can lead to resistant pathogens and harm to non-target organisms and pose health risks. Objectives: This study explored a strategy for minimizing chemical usage by combining biocontrol agents (BCAs) with half-strength fungicide input. Results: In vitro results of fungicide-amended culture plates indicated that the presence of 625 µg mL−1 Azoxystrobin exhibited no growth inhibition of T. atroviride T19 and T. harzianum T16 but increased conidial density of T16 by 90%. Copper (750 µg mL−1) did not suppress the growth of T. virens TVSC or T16 but rather promoted it by 9.5% and 6%, respectively. Additionally, copper increased T16 sporulation by 1.4-fold. Greenhouse trials demonstrated that combining T23 with half-strength Azoxystrobin was as effective as the full dosage in suppressing flower rot. Among the antagonists assessed, Kosakonia sp. exhibited the lowest incidence of fruit rot, whereas T23 resulted in a moderate incidence. Moreover, the combination of T16 or Kosakonia sp. with half-strength copper was almost as effective as the full dosage in reducing fruit rot. Conclusions: Our findings suggest integrating these BCAs in the sustainable management of grey mold in strawberries.